a(lambda(

a(p(

a(a(

a(

a(

lambda(

p(

p(

R

↳Removing Redundant Rules for Innermost Termination

Removing the following rules from

a(lambda(x),y) -> lambda(a(x, p(1, a(y, t))))

a(p(x,y),z) -> p(a(x,z), a(y,z))

a(a(x,y),z) -> a(x, a(y,z))

R

↳RRRI

→TRS2

↳Removing Redundant Rules

Removing the following rules from

a(x,y) ->x

a(x,y) ->y

where the Polynomial interpretation:

was used.

_{ }^{ }POL(lambda(x)_{1})= x _{1}_{ }^{ }_{ }^{ }POL(a(x)_{1}, x_{2})= 1 + x _{1}+ x_{2}_{ }^{ }_{ }^{ }POL(p(x)_{1}, x_{2})= x _{1}+ x_{2}_{ }^{ }

Not all Rules of

R

↳RRRI

→TRS2

↳RRRPolo

→TRS3

↳Removing Redundant Rules

Removing the following rules from

p(x,y) ->y

p(x,y) ->x

where the Polynomial interpretation:

was used.

_{ }^{ }POL(lambda(x)_{1})= x _{1}_{ }^{ }_{ }^{ }POL(p(x)_{1}, x_{2})= 1 + x _{1}+ x_{2}_{ }^{ }

Not all Rules of

R

↳RRRI

→TRS2

↳RRRPolo

→TRS3

↳RRRPolo

...

→TRS4

↳Removing Redundant Rules

Removing the following rules from

lambda(x) ->x

where the Polynomial interpretation:

was used.

_{ }^{ }POL(lambda(x)_{1})= 1 + x _{1}_{ }^{ }

All Rules of

R

↳RRRI

→TRS2

↳RRRPolo

→TRS3

↳RRRPolo

...

→TRS5

↳Dependency Pair Analysis

Duration:

0:00 minutes